Revisão taxonômica de espécies de Scinax duartei (B. Lutz, 1951) (Anura, Hylidae) - Pugliese, Adriana (2002)
A taxonomic population study of the Scinax duartei species complex was undertaken using morphological and morphometrical characters analyses from adults, tadpoles, as well as vocalization parameters. I recognize the complex to be formed by four species: S. duartei (B. Lutz, 1951 ), S. caldarum (B. Lutz, 1968), Scinax sp. nov. "Cipó" and Scinax sp. nov. "Goiás", herein the two former taxa are redescribed while the two latter are described as new. The most evident differences among adults appear in advertisement calls, snout-vent 1ength, shape of the snout, loreal region, and canthus rostralis. For the species of which the tadpoles were described, the differences appear mainly in the total length, skin texture, shape of the snout and lateral line. The distribution of S. duartei expands from Alto Itatiaia, MG (type-locality) and Campos do Jordão, SP, to Aiuruoca, MG. The distribution record of Scinax caldarum (type-locality Poços de Caldas) is enlarged to include Monte Verde and Munhoz, MG, Serra da Bocaina and, Ribeirão Branco, SP. Scinax sp. nov. "Cipó" is recorded from Serra do Cipó (type-locality) to Serra do Caraça, MG. The complex has a large distribution in Southeastern Brazil, being Scinax sp. nov. "Goiás" the only species of the complex know to Central Brazil, in the Chapada dos Veadeiros, GO. Taxonomics notes about the complex are added and compared with literature data.